Hybrid Quantum - Classical AI based approach to solve the Traveling Tournament Problem - Lobo, Desmond; Wagaskar, Kalpita; Gawane, Sarang; Fernandes, Clifford (International Journal of Computer Sciences and Engineering, 2021)
Scheduling has always been deemed as a perfunctory task for most organizations. It could nevertheless become an extremely arduous task if involves the management of events and of the dynamic variables that control it. Herein, we present an idea/solution to the Travelling Tournament Problem (TTP), which is a unique combinatorial problem tackling both feasibility and optimality of the solution. As the TTP belongs to the category of NP-Hard problems, generating solutions usually tend to be extremely costly, with most of the solutions having a time complexity of as high as O(n!). However, two of the many burgeoning fields, artificial intelligence and quantum computing are making headway and we believe that quantum computers possess enough potential to be competent enough to solve such scheduling problems. The aforementioned technologies have provided us with an excellent framework, which we have consequently adopted in our implementation. In the following paper, we portray a hybrid solution that utilizes the immense computational power of a quantum computer while also tweaking the classical algorithm to dynamically reduce the number of iterations and subsequently the cost. We draw parallels between the Travelling Salesman Problem (TSP) and the TTP by utilizing the insights obtained from a detailed analysis of the existing Simulated Annealing based approach, and thus propose certain unique modifications to the best known classical only solutions.